Chapter Parole 'difficili' con un sistema di valutazione automatica. Risposte di italofoni e di non italofoni - Marello, Carla (Strumenti per la didattica e la ricerca, 2021)
This paper is concerned with lexical competence in the study of Italian for academic purposes, notably learned words formed with Greek/Latin elements. To improve and check receptive knowledge of such "difficult" vocabulary both by native and by L2 learners, a number of exercises are made available, and can be actually done and evaluated, at https://esploradizionari.i-learn.unito.it/. This is a technology enhanced learning environment integrating Moodle with the Automatic Assessment System Maple®, a software of Canadian origin already successfully used for teaching STEM disciplines. The specific features of the exercises are discussed, along with early results by Italophone and non-Italophone learners.